2001
DOI: 10.1016/s0022-5347(05)65623-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Gene Expression of Sparc and Its Prognostic Value for Bladder Cancer

Abstract: A significant correlation was detected of the gene expression level of SPARC with histological grade, pathological stage and bladder cancer prognosis. SPARC may have an important role in bladder cancer progression and provide some additional information in patients with bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 14 publications
7
59
0
1
Order By: Relevance
“…9 SPARC has been reported to enhance the invasive capacity of prostate and breast cancer cells, glioma cells, esophageal, bladder and metastatic hepatocellular cancers, invasive meningiomas and malignant melanomas. [24][25][26][27][28][29][30][31][32] In this study, we demonstrated that expression of SPARC is downregulated in colorectal carcinomas. Similar suppression of SPARC has been reported in lung cancer and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
“…9 SPARC has been reported to enhance the invasive capacity of prostate and breast cancer cells, glioma cells, esophageal, bladder and metastatic hepatocellular cancers, invasive meningiomas and malignant melanomas. [24][25][26][27][28][29][30][31][32] In this study, we demonstrated that expression of SPARC is downregulated in colorectal carcinomas. Similar suppression of SPARC has been reported in lung cancer and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to its physiological role, SPARC has been linked to cancer progression as many cancer types present increased levels of SPARC expression upon invasion or metastasis (Rempel et al, 1998;Loging et al, 2000;Bradshaw and Sage, 2001;Framson and Sage, 2004). SPARC is highly expressed in a wide range of human malignant neoplasms, and the deregulated expression of SPARC is often correlated with disease progression and/or poor prognosis (Bellahcene and Castronovo, 1995;Porte et al, 1995Porte et al, , 1998Porter et al, 1995;Massi et al, 1999;Yamanaka et al, 2001). It can interact with different ECM proteins like collagens, matrix metalloproteinases and growth factors modulating the cell shape, growth, adhesion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Elevated SPARC expression is associated with disease progression and poor prognosis in melanoma, breast cancer, glioma, bladder cancer and non-small cell lung cancer. [7][8][9][10][11][12] In colorectal cancer (CRC), the role of SPARC is not well understood. 13,14 SPARC is expressed not only by cancer cells but also by stromal cells surrounding the tumor.…”
Section: Introductionmentioning
confidence: 99%